SISTEM PENGENDALIAN INTERNAL TERHADAP GAJI DAN UPAH PADA DISTRIK NAVIGASI KELAS 1 BELAWAN - Khairani Khairani; Zuliana Zulkarnaen (Worksheet : Jurnal Akuntansi, 2021)
Navigation District is a company engaged in the transportation sector. Everycompany has an internal control system. The purpose of designing an internalcontrol system from a recent perspective that includes a broader scope is essentiallyto protect company property, encourage accuracy and reliability of accountingdata and reporting, increase business effectiveness and efficiency, and encouragecompliance with management policies that have been outlined and regulations. -the rules are there. The type of data used in this research is primary data, namelyqualitative data. The data obtained were collected, interpreted and analyzed thendescribed in detail to find out the problem and seek an explanation. Researchconducted by researchers is primary data obtained directly from the company inthe form of interviews and observations. The purpose of this study was to analyzeand explain the system and procedures for payroll and wages of the Belawan Class1 Navigation District employees and to analyze and explain internal controls in thepayroll and wage systems of employees in the Class 1 Navigation District ofBelawan. The results showed that the payroll procedure that is usually carried outin Belawan Class 1 Navigation District, namely the treasurer makes payroll detailsthen tested by the Commitment Making Officer (PPK) by issuing a paymentapproval letter, after which it is validated by the SPM Signing Officer (PaymentOrder) by issuing a letter. Pay Order (SPM). The SPM main salary is converted bythe State Treasury Service Office (KPPN). After being converted by KPPN, themain salary will be paid to each employee's account. The internal control systemcarried out by the Ministry of Transportation, Directorate General of SeaTransportation, Class 1 Navigation District, Belawan, is controlled by the KPA(Proxy of Budget Users) which is authorized to prepare DPA (BudgetImplementation Documents) , a budget implementation document used as areference for budget users in carrying out government activities as theimplementation of the APBD (State Budget), establishing a PPK (CommitmentMaking Officer), issuing a decree on the appointment of an expenditure treasurer,article 22 (1), (2), (3), KPA may concurrently act as PPK, formulate a system ofsupervision and control so that the process of settling bills at the expense of theAPBD is carried out in accordance with statutory regulations.